The Differential Expression of Mitochondrial Function-Associated Proteins and Antioxidant Enzymes during Bovine Herpesvirus 1 Infection: A Potential Mechanism for Virus Infection-Induced Oxidative Mitochondrial Dysfunction - Xiaotian Fu; Xinyi Jiang; Xinye Chen; Liqian Zhu; Gaiping Zhang (Mediators of Inflammation)
Reactive oxidative species (ROS) are important inflammatory mediators. Electrons escaping from the mitochondrial electron transport chain (ETC) during oxidative phosphorylation (OXPHOS) in the mitochondrial respiratory chain (RC) complexes contribute to ROS production. The cellular antioxidant enzymes are important for maintaining ROS release at the physiological levels. It has been reported that BoHV-1 infection induces overproduction of ROS and oxidative mitochondrial dysfunction in cell cultures. In this study, we found that chemical interruption of RC complexes by TTFA (an inhibitor of RC complex II), NaN3 (an inhibitor of RC complex IV), and oligomycin A (an inhibitor of ATP synthase) consistently decreased virus productive infection, suggesting that the integral processes of RC complexes are important for the virus replication. The virus infection significantly increased the expression of subunit SDHB (succinate dehydrogenase) and MTCO1 (cytochrome c oxidase subunit I), critical components of RC complexes II and IV, respectively. The expression of antioxidant enzymes including superoxide dismutase 1 (SOD1), SOD2, catalase (CAT), and glutathione peroxidase 4 (GPX4) was differentially affected following the virus infection. The protein TFAM (transcription factor A, mitochondrial) stimulated by either nuclear respiratory factor 1 (NRF1) or NRF2 is a key regulator of mitochondrial biogenesis. Interestingly, the virus infection at the late stage (at 16 h after infection) stimulated TFAM expression but decreased the levels of both NRF1 and NRF2, indicating that virus infection activated TFAM signaling independent of either NRF1 or NRF2. Overall, this study provided evidence that BoHV-1 infection altered the expression of molecules associated with RC complexes, antioxidant enzymes, and mitochondrial biogenesis-related signaling NRF1/NRF2/TFAM, which correlated with the previous report that virus infection induces ROS overproduction and mitochondrial dysfunction.